DNA stabilization by the upregulation of estrogen signaling in BRCA gene mutation carriers - Suba Z (Dove Medical Press, 2015)
Zsuzsanna Suba Surgical and Molecular Tumor Pathology Centre, National Institute of Oncology, Budapest, Hungary Abstract: Currently available scientific evidence erroneously suggests that mutagenic weakness or loss of the BRCA1/2 genes may liberate the proliferative effects of estrogen signaling, which provokes DNA damage and genomic instability. Conversely, BRCA mutation seems to be an imbalanced defect, crudely inhibiting the upregulation of estrogen receptor expression and liganded transcriptional activity, whereas estrogen receptor-repressor functions become predominant. In BRCA-proficient cases, estrogen signaling orchestrates the activity of cell proliferation and differentiation with high safety, while upregulating the expression and DNA-stabilizing impact of BRCA genes. In turn, BRCA proteins promote estrogen signaling by proper estrogen synthesis via CYP19 gene regulation and by induction of the appropriate expression and transcriptional activity of estrogen receptors. In this exquisitely organized regulatory system, the dysfunction of each player may jeopardize genome stability and lead to severe chronic diseases, such as cancer development. Female organs, such as breast, endometrium, and ovary, exhibiting regular cyclic proliferative activity are particularly vulnerable in case of disturbances in either estrogen signaling or BRCA-mediated DNA repair. BRCA mutation carrier women may apparently be healthy or exhibit clinical signs of deficient estrogen signaling in spite of hyperestrogenism. Even women who enjoy sufficient compensatory DNA-defending activities are at risk of tumor development because many endogenous and environmental factors may jeopardize the mechanisms of extreme compensatory processes. Natural estrogens have numerous benefits in tumor prevention and therapy even in BRCA mutation carriers. There are no toxic effects even in sky-high doses and all physiologic cellular functions are strongly upregulated, while malignant tumor cells are recognized and killed in a Janus-faced manner. Keywords: BRCA1/2 mutations, breast cancer, estrogen receptors, ER signaling, genome stabilization, cancer prevention